An Ecological study of Epiphytic algae on the aquatic plants Ceratophyllum demersum and Phragmites australis in depression of Bahr AL-Najaf Iraq. - M. Alkam, Foad; J. Al-Shammary, Athraa; Y. Hafed, Ali (Al-Qadisiyah Journal of Pure Science, 2018)
The present study included some of physical and chemical charcters for water of Bahr Al-Najaf and it’s effect on epiphytic algae on some aquatic plants for period from October 2015 to April 2016 , Three station were chosen in the present study . the first station locates on the westerly of Najaf city in Agricultural area . whereas the second and third stations lies besides of strategic line for oil . Two kinds of aquatic plants were chosen for diagnosing epiphytic algae on it (Ceratophyllum demersum and Phragmites australis). The results of present study showed that Air and Water temperature valued between (15-33)CÂ° and (12-27.1)CÂ° , Results revealed that water of Baher Al-Najaf was slightly alkaline and has good Oxygen content ranged between (1.02-13.8)mg/l , while BOD ranged between (0.77-13.54)mg/l , which means that water in first station were organically polluted , CO2 concentrations ranged between (98-290)mg/l , EC values ranged between (8849-94587)Âµc/cm whereas values of Nitrate ranged between (1.77-139)Âµg/l , and Phosphate ranged between (ND-0.53) Âµg/l. Diagnosing of epiphytic algae on both aquatic plants reached to 289 species , The predominant was for Bacillariophyceae class with 130 species about 44.98% , Followed by Cyanophyceae with 99 species and 34.20% , and Chlorophyceae with 39 species and 13.49% , Followed by Euglenophyceae 17 species and 5.88% , and recorded one species about 0.35% for every class of Cryptophyceae , Crysophyceae , Rhodophyceae and Xanthophyceae. Also noticed that the number of diagnosing epiphytic algae on Phragmites were Higher than Ceratophyllum in the present study for all study station , and The genera Navicula from Diatomes and Oscillatoria from Cyanophyceae were predominant in all study stations.